PENGARUH KINERJA KEUANGAN DAN BELANJA MODAL TERHADAP PERTUMBUHAN EKONOMI PADA KABUPATEN/KOTA DI JAWA TENGAH - Pradiatmi, Istia Nur; Wibowo, Hardiyanto (Universitas Muhammadiyah Malang)
This research was quantitative research that aims to determine the effect of financial such asthe ratio of decentralization degree, the dependency ratio, the independent ratio, effectivenessratio, the ratio of the contribution degree of Regional Owned Enterpise (BUMD) , efficiency ratio,and the ratio of expenditure harmony as well as capital expenditure to economic growth. Thepopulation of the study was the regencies/cities in Central Java. The sample of study wereselected using census method and obtained 175 observation sample. The analysis techniqueapplied in this reseach was multiple linear regretion analysis. This analysis proved that theratio of variable degree of decentralization positively and significantly affected on economicgrowth with significant score of 0,009 < 0,05. Dependency ratio variable significantly and negatively affected on economic growth with significant score of 0,004 < 0,05. Independent ratiovariable significantly and negatively affected on economic growth with significant score of 0,000< 0,05. Effectiveness ratio variable did not affect the economic growth with significant score of0,240 > 0,05. The degree of regional owned enterpise contribution variable did not affect theeconomic growth with significant score of 0,454 > 0,05. Efficiency ratio variable did not affect theeconomic growth with significant score of 0,419 > 0,05. Ratio variable of compatible expendituredid not affect the economic growth with significant score of 0,341 > 0,05. However, the capitalexpenditure variable did not affect the economic growth with significant score of 0,098 > 0,05.Keyword: financial performance, capital expenditure, and economic growth